2016
DOI: 10.1210/jc.2015-4147
|View full text |Cite
|
Sign up to set email alerts
|

Imbalance of Amniotic Fluid Activin-A and Follistatin in Intraamniotic Infection, Inflammation, and Preterm Birth

Abstract: Activin-A and follistatin are part of the complex inflammatory response of the gestational sac to infection and modulate effector pathways leading to PTB. The activin-A to follistatin ratio may play a role in determining the clinical phenotype of PTB as preterm labor or PPROM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 43 publications
0
18
0
Order By: Relevance
“…ActRIIA is a transmembrane protein expressed on the surface of cell membranes. Activin signaling first activates ActRIIA, which phosphorylates type I receptors and then regulates the transcription of target genes through signal transduction via Smad classical or non-SMAD pathways [ 11 , 12 ]. The flow cytometry results showed that ActRIIA expression on CD8 + T cells and CD19 + B cells was increased in the Kawasaki disease group compared with the healthy control group.…”
Section: Resultsmentioning
confidence: 99%
“…ActRIIA is a transmembrane protein expressed on the surface of cell membranes. Activin signaling first activates ActRIIA, which phosphorylates type I receptors and then regulates the transcription of target genes through signal transduction via Smad classical or non-SMAD pathways [ 11 , 12 ]. The flow cytometry results showed that ActRIIA expression on CD8 + T cells and CD19 + B cells was increased in the Kawasaki disease group compared with the healthy control group.…”
Section: Resultsmentioning
confidence: 99%
“…An increasing number of clinical studies have reported that activin A levels are markedly elevated during the various bacterial infections, including sepsis, meningitis and intra-amniotic infection, and so on ( Ebert et al., 2006 ; Hardy et al., 2016 ; Lee et al., 2016 ; Michel et al., 2003 ; Petrakou et al., 2013 ; Rosenberg et al., 2012 ; Wilms et al., 2010 ). Higher levels of serum activin A have been observed in patients with sepsis compared to healthy volunteers, and activin A levels were correlated with disease severity in these patients, suggesting that activin A may serve as a potential diagnostic marker for sepsis severity ( Lee et al., 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to activin, FS has an anti-inflammatory response by direct inhibition of activin (29). The imbalance between activin and FS exaggerates the severity of the inflammatory state in diseases such as asthma and carcinogenesis (30). The release of activin precedes the release of other inflammatory cytokines, therefore the modulation of the activin and FS system is a potential therapeutic target in HIVassociated PE which has an inflammatory component (30).…”
Section: Discussionmentioning
confidence: 99%
“…The imbalance between activin and FS exaggerates the severity of the inflammatory state in diseases such as asthma and carcinogenesis (30). The release of activin precedes the release of other inflammatory cytokines, therefore the modulation of the activin and FS system is a potential therapeutic target in HIVassociated PE which has an inflammatory component (30). The non-significant difference in FS expression in this study may be attributed to the use of highly active antiretroviral therapy (HAART), a standard of care in all HIV infected patients in SA.…”
Section: Discussionmentioning
confidence: 99%